Public goods and ethnic divisions - Alesina, Alberto; Easterly, William; Baqir, Reza (1999)
We present a model that links heterogeneity of preferences across ethnic groups in a city to the amount and type of public goods the city supplies. We test the implications of the model with three related data sets: U.S. cities, U.S. metropolitan areas, and U.S. urban counties. Results show that the shares of spending on productive public goods - education, roads, sewers and trash pickup - in U.S. cities (metro areas/urban counties) are inversely related to the city's (metro area's/county's) ethnic fragmentation, even after controlling for other socioeconomic and demographic determinants. We conclude that ethnic conflict is an important determinant of local public finances. - Reproduced
Keywords: Public goods - United States; Public utilities - United States; Public utilities